2015
DOI: 10.1097/pec.0000000000000336
|View full text |Cite
|
Sign up to set email alerts
|

Child Mental Health Services in the Emergency Department

Abstract: The ED is an entry point into the child mental health system of care for children with Medicaid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Increased use of the ED has previously been observed in the Medicaid population. [18][19][20] Although this study was not designed to compare Medicaid versus private insurance, our results confirm that the ED is frequently used by the Medicaid population.…”
Section: Discussionsupporting
confidence: 72%
“…Increased use of the ED has previously been observed in the Medicaid population. [18][19][20] Although this study was not designed to compare Medicaid versus private insurance, our results confirm that the ED is frequently used by the Medicaid population.…”
Section: Discussionsupporting
confidence: 72%
“…In the literature, little information emerges regarding hospitalization trends [ 13 ]. Nonetheless, the demographic and clinical factors most associated with psychiatric hospitalizations during child development appear to be adolescence, suicidal ideation and/or suicide attempts (more frequent among females), psychomotor agitation (more frequent among males), a psychiatric family history, past hospitalizations, psychiatric comorbidity, a history of victimization (bullying, physical, psychological, and/or sexual abuse, neglect, and witnessing violence), and academic and relational difficulties [ 2 , 7 , 14 , 15 , 16 , 17 , 18 ]. In particular, a large number of studies identify parental psychiatric illness as one of the most significant risk factors for pediatric-age psychiatric hospitalization [ 16 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The previous literature on mental health ED visits highlight specific categories like suicide, mood disorders, behavioral disorders, and substance use/abuse, but few have provided a current in-depth assessment of mental health categories especially within pediatric and American Indian populations. 10, 16, 25 We found that the depressive disorder category was most common for older American Indian children. Similar to our results, one previous study found that adjustment disorders as well as post-traumatic stress disorder were common among urban American Indian and Alaska Native Youth receiving mental health services.…”
Section: Discussionmentioning
confidence: 68%
“…Other studies have found lower prevalence for younger children as well. 7, 25 The reason for this difference is unclear, but we hypothesize that the mental health conditions are present but are not being recognized or screened properly. We also believe this is exacerbated for American Indian children due to differential access to mental health providers and financial constraints.…”
Section: Discussionmentioning
confidence: 96%